PENGARUH SISTEM REWARD DAN MOTIVASI KARYAWAN TERHADAP KINERJA KARYAWAN (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study aims to analyze the effect of reward systems and employee motivation on employee performance. The sample obtained was 36 respondents, the sampling technique uses probability sampling, which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as sample members. . This study uses a census approach, where all members of the population serve as respondents with 36 employees of PT. Wahyu Tehnik Utama. The results showed that there was an effect of the reward system on employee performance. This proves the hypothesis which states that there is a significant influence between the reward system on employee performance and employee motivation has a significant effect on employee performance.